Delaunay Mesh Generation - Cheng, Siu-Wing; Dey, Tamal K; Shewchuk, Jonathan (Chapman & Hall/CRC Computer and Information Science Series, 2012)
Written by authors at the forefront of modern algorithms research, this book demonstrates the power and versatility of Delaunay meshers in tackling complex geometric domains ranging from polyhedra with internal boundaries to piecewise smooth surfaces. It is one of the first to integrate a vast amount of cutting-edge material on Delaunay triangulations. Covering both volume and surface meshes, the book offers a rigorous theoretical analysis of mesh generation methods while also showing how the algorithms work well in practice.